99Tc-MDP maintains bone mineral density for postmenopausal differentiated thyroid cancer patients with osteopenia under thyroid-stimulating hormone suppression - Zhang, Yuanfang; Wang, Yingqiu; Sun, Donghua; Ma, Chao (Frontiers in Endocrinology, 2025)
BackgroundThe main determinant of skeletal fragility in postmenopausal patients with differentiated thyroid cancer (DTC) and osteopenia is thyroid-stimulating hormone (TSH) suppressive therapy. Evidence for the use of bisphosphonates, including technetium-99 methylene diphosphonate (99Tc-MDP), in this clinical setting remains limited. ObjectiveTo investigate the effects of 99Tc-MDP on osteopenia (T-score <-1.0≥-2.5 SD for the lumbar spine by DXA) in postmenopausal women with DTC under TSH suppression therapy compared with routine calcium/vitamin D supplementation.MethodsA total of 102 postmenopausal patients with DTC and osteopenia under TSH suppression therapy were enrolled in this open-label, prospective study. Patients were divided into two groups: calcium/vitamin D supplements (groupCa) and calcium/vitamin D plus 99Tc-MDP (groupmdp) groups. Lumbar spine bone mineral density (BMD) by DXA was measured before and 12 months after treatment. Bone turnover markers were evaluated at baseline, 6 months, and 12 months.ResultsThe combined 99Tc-MDP treatment significantly increased the mean percentage change of lumbar BMD at month 12 compared with groupCa (t=2.156, p=0.035). A significant decrease in BMD of the lumber spine from 0.9148 ± 0.08 to 0.8726 ± 0.08 (t=3.81, p=0.001) at month 12 was observed in groupCa. The mean percentage change from baseline in the levels of serum β-isomer of C-terminal telopeptide of type I collagen (β-CTX), procollagen type 1 N-terminal propeptide (P1NP) showed that 99Tc-MDP combined treatment significantly increased PINP at month 6 (t=2.37, p = 0.02) and 12 (t=2.224, p = 0.029), and significantly decreased β-CTX at month 12 (t=-2.746, p = 0.008) compared with groupCa. No severe adverse events were reported in either group. Conclusions99Tc-MDP is safe and could maintain lumbar BMD in postmenopausal women with DTC and osteopenia under TSH suppression therapy during a 1-year follow-up. Calcium/vitamin D supplementation alone did not effectively prevent bone loss in these patients.Trial registration numberChiCTR2200064170